Urea in cancer patients with chronic SIAD‐induced hyponatremia: Old drug, new evidence. (29th March 2019) - Nervo, Alice; D'Angelo, Valentina; Rosso, Daniela; Castellana, Eleonora; Cattel, Francesco; Arvat, Emanuela; Grossi, Emidio
Summary: Background: Syndrome of inappropriate antidiuresis (SIAD) is the main cause of hyponatremia in cancer patients. International guidelines indicate urea as an interesting option for chronic SIAD. Nevertheless, strong data to support its use are lacking, and its role in oncologic patients has not been described so far. Material and Methods: We retrospectively analysed 36 cancer patients affected by moderate or profound SIAD‐induced chronic hyponatremia, who started oral urea (initial daily dose 15 g or 30 g) without fluid restriction between July 2013 and July 2018. We analysed mean serum sodium (sNa) increase after 24 hours and percentages of patients who reached eunatremia within 14, 30 and 60 days of treatment, stratifying according to the degree of hyponatremia at diagnosis. Clinical evaluation and biochemical assessment were periodically performed. Results: Mean sNa was 123 [±4] mmol/L at baseline; after 24 hours of treatment, a mean increase of 5 [±3] mmol/L was observed. Eunatremia was reached by 55.6%, 86.1% and 91.7% patients within 14, 30 and 60 days of treatment, respectively. Trends in sNa normalization were similar in patients with moderate and profound hyponatremia at diagnosis. Rapid sNa overcorrection was avoided in all cases. Urea  was interrupted within  the first  2 months  of treatment in 10 patients, in half cases for rapid neoplastic progression and in the remaining patients for the drug taste. Conclusions: In our study, urea was effective in correcting chronic hyponatremia among cancer patients with SIAD. Almost all patients reached eunatremia within the first month of therapy, and urea was globally well tolerated.